Streptococcus Pneumoniae Bacteremia with Acute Kidney Injury and Transient ADAMTS13 Deficiency - Sam Van Hove; Alexis Werion; Ahalieyah Anantharajah; Leila Belkhir; Marie-Astrid van Dievoet; Philippe Hantson (Case Reports in Infectious Diseases)
A 43-year-old woman with a medical history of splenectomy for immune thrombocytopenic purpura was diagnosed with Streptococcus pneumoniae bacteremia. Her initial complaints were fever and more importantly painful extremities that appeared cyanotic. During her hospitalisation, she never developed cardiocirculatory failure but presented acute kidney injury (AKI) with oliguria. Laboratory investigations confirmed AKI with serum creatinine 2.55 mg/dL which peaked at 6.49 mg/dL. There was also evidence for disseminated intravascular coagulation (DIC) with decreased platelet count, low fibrinogen levels, and high D-dimer levels. There were no signs of haemolytic anaemia. The initial ADAMTS13 activity was low (17%) but slowly recovered. Renal function progressively improved with supportive therapy, as opposed to the progressing skin necrosis. The association of DIC and low ADAMTS13 activity may have contributed to the severity of microthrombotic complications, even in the absence of thrombotic microangiopathy as thrombotic thrombocytopenic purpura (TTP) or pneumococcal-associated haemolytic uremic syndrome (pa-HUS).